Performing the Theatricality in the Game of Framings: rethinking the weaving of the dramatic - Arruda (Universidade Vila Velha ‒ UVV, Vila Velha/ES, Brazil), Rejane (Revista Brasileira de Estudos da Presença, 2022)
Through the analysis of contemporary propositions and postulating the game of framings as the principle of scene poetics building, this article analyzes the notions of theatricality and performativity as co-existing functions. Displaced from the field of theater criticism to the performance, theatricality and performativity appear as operational notions of an analysis of the actorly praxis, providing the basis for a review of theory and the place of the dramatics as an alleged practice of signification, allowing its presentation as a framing mode among others.